Developing a high-fidelity simulated-learning environment (SLE) in audiology education: a preliminary investigation - Dzulkarnain, Ahmad Aidil Arafat; Mohd Puzi, Nur Ain Fathanah; Rahmat, Sarah; Badzis, Mastura; Che Azemin, Mohd Zulfaezal (2017)
Purpose of the study: To update on the development of high-fidelity simulated learning environment (SLE) training module in audiology education. Methods: Two audiology clinical preceptors and four experts in computer software engineering were involved in this development. The audiology clinical preceptors outlined the high-fidelity training module needed for pre-clinical training for 2nd year undergraduate students. These involved history taking, otoscopic examination, pure tone audiometry and acoustic immitance. The proposed module consists of simulation that involved psychomotor, cognitive, social and affective learning domains and a comprehensive feedback module. Results: The newly high-fidelity SLE training module has been fully developed and in the midst of validation and to be pilot among audiology instructors and students. Conclusion: The newly SLE high-fidelity SLE training has a high potential to be used among clinical audiology student in particular to prepare them for actual clinical training